2019
DOI: 10.2478/fco-2019-0003
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Registry Report in Mansoura University Hospital, Egypt in 2015

Abstract: BackgroundThis study aimed to report a cancer registry in Clinical Oncology and Nuclear Medicine Department, Mansoura University Hospital in 2015.Patients and MethodsAll cancer patients who were registered in the department of Clinical Oncology and Nuclear Medicine, Mansoura University Hospital in the time period from January 1st, 2015 to December 31st, 2015, were enrolled in this study. The data in the outpa­tient clinic index including patient’s name, age, sex and diagnosis were collected.ResultsThe included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…Overall, the studies were of acceptable methodological quality, where 18 studies 15 , 17 , 23 , 24 , 27 - 29 , 31 - 36 , 39 - 41 , 43 , 44 were scored good, four studies scored very good, 22 , 30 , 37 , 42 and four studies scored satisfactory. 16 , 25 , 26 , 38 Funnel plots were generated for the included studies in the analysis for the AJCC stages, where the visual assessment showed relatively symmetrical plots with no evidence of publication bias (Data Supplement [Appendix Figure 1]).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Overall, the studies were of acceptable methodological quality, where 18 studies 15 , 17 , 23 , 24 , 27 - 29 , 31 - 36 , 39 - 41 , 43 , 44 were scored good, four studies scored very good, 22 , 30 , 37 , 42 and four studies scored satisfactory. 16 , 25 , 26 , 38 Funnel plots were generated for the included studies in the analysis for the AJCC stages, where the visual assessment showed relatively symmetrical plots with no evidence of publication bias (Data Supplement [Appendix Figure 1]).…”
Section: Resultsmentioning
confidence: 92%
“…Figure 1 depicts the PRISMA flow chart for the search strategy. Three studies 30 , 32 , 37 presented data extracted from population-based cancer registries, while other three studies 22 , 28 , 42 were based on hospital-based cancer registries. Furthermore, 16 studies 16 , 17 , 24 - 26 , 31 , 33 - 36 , 38 - 41 , 43 , 44 had collected data retrospectively and three studies 23 , 27 , 29 were cross-sectional studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Egypt gastric cancer represents the 14th most common cancer, accounting for 18% of cases in both sexes [7]. According to cancer registry report in Mansoura university hospital, during 2015, Cancer stomach represents only 1.8% of frequencies of all the cancer sites [8]. Thus, explaining the limited number of patients in our study.…”
Section: Discussionmentioning
confidence: 75%
“…In Egypt, GC is the 12th frequent cancer for both sexes, accounting for 1.6 percent of all cancer cases in 2015, with an estimated 1271 new patients [2]. The rate of occurrence varies by location in Egypt, with Upper Egypt having the greatest rate (2.48 percent) and Lower Egypt having the lowest rate (0.98 percent).also in the clinical oncology department of Mansoura University, reported 47 cases (1.79%) out of 2620 cases totally at 2015 [3].…”
Section: Introductionmentioning
confidence: 99%